2014
DOI: 10.1001/jamaoto.2014.341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Test Battery to Assess Perception of Music in Children With Cochlear Implants

Abstract: The MCCI provided an efficient and user-friendly assessment of music perception in pediatric CI users. This test battery may serve as a valuable tool to evaluate music perceptual abilities of pediatric CI users and measure the effects of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…CI listeners perceive pitch less accurately than normal-hearing (NH) listeners (Pretorius and Hanekom, 2008; Kang et al, 2009), as well as other spectral parameters in music, such as melody contour (Galvin et al, 2009) and instrument timbre (Kang et al, 2009; Brockmeier et al, 2011). Roy et al (2014) found similar results in CI children, who exhibited difficulty in discriminating pitch and timbre, but less so for discriminating chord sequences.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…CI listeners perceive pitch less accurately than normal-hearing (NH) listeners (Pretorius and Hanekom, 2008; Kang et al, 2009), as well as other spectral parameters in music, such as melody contour (Galvin et al, 2009) and instrument timbre (Kang et al, 2009; Brockmeier et al, 2011). Roy et al (2014) found similar results in CI children, who exhibited difficulty in discriminating pitch and timbre, but less so for discriminating chord sequences.…”
Section: Introductionsupporting
confidence: 56%
“…Taken this small difference into account, an even larger discrepancy between the two groups might therefore have been expected. In some cases, children listening through a CI have been reported to discriminate chords on the same level as their NH peers (Roy et al, 2014). In their experiment, the target chords were framed by harmonically related major chords.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the adult version of the test, all music was played by piano whereas the child version contains 10 instruments (including piano) to help maintain test engagement (Peretz et al, 2013). It is clear that children using CIs have more difficulties than their normal hearing peers distinguishing between different instruments (Roy et al, 2014) but potential effects of different instruments on cMBEA performance in either group of children has not been studied to our knowledge.…”
Section: The Montreal Battery Of Evaluation Of Amusia For Testing Musmentioning
confidence: 99%